Pengaruh Profitabilitas (ROA), Likuiditas (AKO), Ukuran Perusahaan (SIZE), dan Leverage (LTDER) terhadap Nilai Perusahaan - Vannessa Natalie; G. Anggana Lisiantara (Owner : Riset dan Jurnal Akuntansi, 2022)
Firm value is the investor's perception of a company related to stock prices. High company value will make the market not only believe in the company's current performance, but also on its future prospects. In the preparation of this study, the aim was to examine and analyze the effect of profitability, liquidity, company size, and leverage on firm value in property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This study uses a population of all property and real estate companies that have been listed on the Indonesia Stock Exchange (IDX) in the last five periods, namely 2017-2021. The sample selection method used in this study was a purposive sampling technique with several selected criteria, so as to obtain a sample of 105 companies. This study uses secondary data in the form of numbers that are processed into a statistical measurement scale, so it is called secondary data. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that profitability (ROA) and firm size (SIZE) have no effect on firm value, liquidity (AKO) has a positive and significant effect on firm value, while leverage (LTDER)  has a negative and significant effect on firm value.